Aromatic Metamorphosis of Dibenzothiophenes - Yorimitsu, Hideki; Vasu, Dhananjayan; Bhanuchandra, M.; Murakami, Kei; Osuka, Atsuhiro (Synlett, 2016)
In general, aromatic cores are stable owing to their resonance energies. Different from facile peripheral modifications of aromatic cores, transforming an aromatic core into a different skeleton is ambitious and has attracted only little attention as a general synthetic method. This personal account shows our journey to inventing transformations of dibenzothiophenes into triphenylenes, carbazoles, and spirocyclic diarylfluorenes and to establishing ‘aromatic metamorphosis’ as a useful and game-changing strategy in organic synthesis.1 Introduction2 Aromatic Metamorphosis3 From Dibenzothiophenes to Triphenylenes4 From Dibenzothiophenes to Carbazoles5 From Dibenzothiophenes to Spirocyclic Tetraarylmethanes6 Conclusion
Keywords: dibenzothiophenes; palladium; arylations; nucleophilic aromatic substitution; umpolung